English language Teaching and Learning through Language Laboratory in Technical Institutes - Tiwari, Mrs. Sarika Srivastava; Batra, Dr J.C (IJRDO- Journal of Educational Research, 2016)
The ability to communicate effectively has become the prerequisite for anyone who ventures into a new profession; the need for developing communication skills is a much-felt phenomenon today. Both governmental and private institutions are focusing their attention on students developing their communicative skills. As technology has entered into every aspect of human life, it has extended its advanced products into the field of language learning also; The main objective of the present article is to highlight the importance of language lab in learning communication skills by using advance techniques in learning process. Language learning is not the same as learning any other subject; it is not confined up to spoken English only. The four skills of listening, speaking, reading and writing must have to be practiced and learned well. In which language lab can play an important role. As it is a technological aid for learning, it has a number of advanced facilities that can help students to learn a language with proficiency to communicate. This article focuses on Concept of language lab, types of laboratory, and how learning through language lab could be easy and interesting,